Turnover Intention Analysis of Health Human Resources at PT AEA - Imanuel, Bobby Andreas; Sumardjo, Mahendro; Jubaedah, Jubaedah; Supriadi, Yudi Nur (Garuda Prestasi Nusantara Consulting, 2022)
The competition in the field of health service is diverse and competitive. When facing the competition with the competitor, the quality of health services must also on it's prime. One of the factor that determine the quality of service is the quality of the human resource. But to provide the most excellent service with the lowest price, competitor is offering higher salary to the human resources of PT.AEA. In this case, employment turnover is giving a negative impact to the company because of the health human resources recruited by the competitor is getting a training and debriefing. The high rate of employment turnover has resulted in the decreased of company performance and incurring cost on the recruitment of new employees. Therefore, every company must analyze and control the factor that cause the high rate of human resources turnover. Keywords : Human resource, health service, employee turnover